2018
DOI: 10.18273/revsal.v50n1-2018006
|View full text |Cite
|
Sign up to set email alerts
|

Riesgo cardiovascular en una población adolescente de Timbío, Colombia

Abstract: ResumenIntroducción: Las enfermedades cardiovasculares se encuentran entre las primeras causas de muerte a nivel mundial y la evidencia científica sugiere que tienen un origen en edades tempranas, por lo que disminuir desde la adolescencia los riesgos que contribuyen a su aparición es indispensable. Objetivo: Determinar riesgo cardiovascular en la población adolescente de una institución educativa de Timbío, Cauca, 2015-2016. Metodología: Estudio cuantitativo, descriptivo, observacional y de corte transversal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…reported a high level of physical activity of 79 % in individuals living in rural areas, where people are characteristically involved in farming activities, among others, besides traveling long distances between their homes and the educational institutions (29).…”
Section: Discussionmentioning
confidence: 99%
“…reported a high level of physical activity of 79 % in individuals living in rural areas, where people are characteristically involved in farming activities, among others, besides traveling long distances between their homes and the educational institutions (29).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos anteriores (GROS, 1992;ESPINOSA, 1995, RAPPAPORT, 2000RUANO, 2016) confirmam que o endereçamento de cartas abertas é uma ação política indígena de reconhecida trajetória. A carta aberta encaminhada pela Minga se configurou como uma ação, com certo caráter conservador, em resposta ao contexto de criminalização do governo Uribe.…”
Section: O Repertório Cultural Da Mingaunclassified
“…Espinosa (1995) advertiu que as marchas indígenas possibilitam a experimentação social demarcada pela busca de informação e reconhecimento identitário. Para Rappaport (2000), durante os deslocamentos alcançados nas marchas o território nativo é reafirmado, no entendimento dele como campo de forças em disputa.…”
Section: A Marcha No Repertório De Protesto Indígenaunclassified
See 1 more Smart Citation
“…In [10], a study was carried out in an educational institution of 100 schoolchildren from 10 to 19 years old, with the aim of determining cardiovascular risk. The study found a prevalence of cardiovascular risk of 84.6% in adolescents (15-18 years old), as well as that the consumption of alcoholic beverages and unhealthy eating habits are related to the increase in cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%